Non-uniform Effects of Nociceptive Stimulation to Motoneurones during Experimental Muscle Pain. (21st May 2021) - Hodges, Paul W.; Butler, Jane; Tucker, Kylie; MacDonell, Christopher W.; Poortvliet, Peter; Schabrun, Siobhan; Hug, François; Garland, S. Jayne
Highlights: It is widely believed that pain/nociception lead to inhibition of a painful muscle. Two independent methods were used to estimate changes in motoneurone excitability. Results do not support the hypothesis of uniform inhibition of a painful muscle. Results suggest redistribution of activity between motor units. This interpretation differs from the general view of adaptation to motor function. Abstract: Nociceptive stimulation is predicted to uniformly inhibit motoneurone pools of painful muscles and those producing painful movements. Although reduced motoneurone discharge rate during pain provides some evidence, recent data show evidence of increased excitability of some motoneurones. These observations suggest non-uniform effects of nociception on motoneurone excitability. More direct measures are required, but this is difficult to assess as few measures enable in vivo evaluation of motoneurone excitability in humans. We investigated changes in motoneurone excitability during experimental pain using two methods in separate experiments: (i) estimation of the time-course of motoneurone afterhyperpolarization (AHP) from interval death rate analysis of interspike intervals of single motor unit discharge; and (ii) probability of early motoneurone discharge to a descending volley excited using transcranial magnetic stimulation (TMS). Tibialis anterior motor units were recorded with fine-wire electrodes before, during and after painful infusion of 5% hypertonic saline into the muscle. Activation of 17 units (16 participants) could be used for AHP analysis. Data show shortened ( n  = 11) and lengthened ( n  = 6) AHP time-course. Increased ( n  = 6) and decreased ( n  = 6) probability of early motoneurone discharge were observed in the TMS experiment. These convergent observations suggest non-uniform effects of nociceptive stimulation on motoneurone pools. This does not support the hypothesis that nociceptive input induces uniform inhibition of painful muscle. Instead, interpretation of results implies redistribution of activity between motor units, with possible benefit for unloading painful tissues. This finding supports an interpretation that differs from the generally accepted view in pain physiology regarding adaptation to motor function in pain.